Synthesis and Biological Activities of Substituted 1,2-Diazole Derivatives - Singh, C.P. (Asian Journal of Chemistry, 2010)
The synthesis and biological activities (antiinflammatory and antimicrobial) of a number of 1,2-diazole derivatives are described. N1 - nicotinoyl-3-methyl-5-phenyl-4-sulpha/substituted phenylazo-1,2-diazoles have been synthesised by the condensation of sulpha substituted phenylazo-1-phenyl-1,3-butanedione with nicotinic acid hydrazide, using glacial acetic acid as condensing agent. Pharmacological profile of the compounds synthesised is described.